2009
DOI: 10.1002/clc.20446
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Intervention of Superior Mesenteric Artery Stenosis in Elderly Patients

Abstract: This review article focuses on stent placement in mesenteric arteries in older patients with an increasingly common diagnosis of chronic mesenteric ischemia (CMI). We reviewed the articles that focused on the treatment of this gastrointestinal disorder by stenting/open surgical revascularization to avoid further ischemic episodes and bowel infarction and necrosis. The advantages of stent placement in mesenteric arteries are discussed in comparison to open surgical revascularization. In summary, the low morbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Mechanical factors have been implicated as the causes of vessel wall trauma during atherectomy. These include the tortuous nature of the vessel, an oversized atherectomy device, lesions close to a prior surgical scar, and the location of the lesion near the side branches [ 13 ]. These factors can lead to a deeper cut than intended for a diseased vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical factors have been implicated as the causes of vessel wall trauma during atherectomy. These include the tortuous nature of the vessel, an oversized atherectomy device, lesions close to a prior surgical scar, and the location of the lesion near the side branches [ 13 ]. These factors can lead to a deeper cut than intended for a diseased vessel.…”
Section: Discussionmentioning
confidence: 99%
“…A recent population-based research found that 17.5% of an elderly, free-living cohort had asymptomatic celiac axis (CA) or superior mesenteric artery (SMA) stenosis at duplex ultrasound (US) [ 11 , 12 ]. Only 2.5% of the participants had SMA disease, although it was linked with weight loss and renal artery stenosis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Las opciones de tratamiento para la trombosis aguda centrada en métodos quirúrgicos han cambiado poco desde el siglo 20. Algunos pacientes pueden ser buenos candidatos para angioplastia percutánea transluminal con la colocación de stents (5)(6)(7)(8)(9)(10) . Otra alternativa sería la terapia trombolítica si los pacientes no llevan más de 8 horas de presentación de los síntomas y no tienen signos de peritonitis ni necrosis intestinal (11) .…”
Section: Introductionunclassified